(untitled) (Bangladesh Pharmaceutical Journal, 2015)
Traditionally metoclopramide hydrochloride is used as an antiemetic in migraine & cancer patients and in controlling post-operative nausea and vomiting. The main aim of this study was to develop a swellable oral thin film for the treatment of the mentioned pathological conditions. This swellable thin film formulation is specially designed for paediatric patients for oral administration, where it will swell up when exposed to saliva in the oral cavity and will be easily swallowed by the patient, without the need for water. Nine formulations of swellable oral thin film of metoclopramide hydrochloride such as F1 to F9 were prepared by solvent casting method. The drug-Povidone K90 ratio were 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 and 1:9, respectively. Various physicochemical evaluations including weight variation, thickness, folding endurance, in vitro dissolution studies, content uniformity, FTIR, Trinocular microscopic imaging and swelling property of film were conducted. It was observed that thickness and weight of film was directly proportional to the total solid content of the film (F1 showed the lowest thickness and weight and F9 showed the highest). All the batches revealed content uniformity between 98.0% to 101.0% and cumulative drug release between 94.8% and 102.4%. Swelling behavior of film was inversely proportional to the quantity of Povidone K90 in the film. Formulation F1 showed the highest linear expansion co-efficient (L%) and percentage increase in weight due to swelling while F9 demonstrated the lowest corresponding to the quantity of Povidone K90. Quantity of glycerin and Povidone K90 affected the appearance and peeling of the films. F1, F2 and F3 had lowest quantity of glycerin and Povidone K90 and were least glossy and easier to peel out and F7, F8 and F9 with highest quantity of glycerin and Povidone K90 and were glossiest but hardest to peel out. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22325 Bangladesh Pharmaceutical Journal 17(1): 102-112, 2014